2015
DOI: 10.1111/aos.12808
|View full text |Cite
|
Sign up to set email alerts
|

Distance‐ and near‐visual impairment in rural Chinese adults in Kailu, Inner Mongolia

Abstract: ABSTRACT.Purpose: To investigate the prevalence and causes of distance-visual impairment and near-vision impairment in a rural Chinese population in Inner Mongolia. Methods: A population-based, cross-sectional study design was used to identify visual impairment in the Chinese aged 40 years and older living in Kailu County, Inner Mongolia. Low vision, blindness and near-visual impairment (NVI) were defined according to World Health Organization (WHO) criteria. Results: The overall prevalence of blindness and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
0
39
2
Order By: Relevance
“…On the other hand, the prevalence of low vision (5.7%) in our study was slightly higher than those in Baotou (3.7%)3 and Kailu (4.7%) 4. Nevertheless, the study sample for Baotou and Kailu studies were aged 40 years and above.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, the prevalence of low vision (5.7%) in our study was slightly higher than those in Baotou (3.7%)3 and Kailu (4.7%) 4. Nevertheless, the study sample for Baotou and Kailu studies were aged 40 years and above.…”
Section: Discussioncontrasting
confidence: 79%
“…Another study in Kailu, northern Inner Mongolia, reported that the prevalence of blindness and VI based on best-corrected visual acuity (BCVA) was 0.9% and 4.7%, respectively. The leading cause of VI and blindness in Kailu was also cataract 4. However, barriers to cataract surgery and cataract surgery-related outcomes were not investigated in these previous studies.…”
Section: Introductionmentioning
confidence: 97%
“…[8] The studies estimating the prevalence of blindness and low vision in China published from January 2010 to April 2016 were searched and presented in Table 6. [4,920] Although the estimating criteria for blindness and low vision differed among studies, Table 6 shows that according to the BCVA in better eye, previous studies reported that the prevalence rates of blindness and low vision were 0.2% to 2.88% and 1.4% to 10.41% in China, respectively. In rural of Kailu County, Inner Mongolia, the overall prevalence rates of blindness and low vision based on BCVA were 0.9% and 7.52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In the rural Chinese population in Kailu which is a county in Tongliao city of Inner Mongolia, the overall prevalence rates of visual impairment and blindness using presenting visual acuity (PVA) were 9.8% and 2.2%, respectively, and were adjusted to 4.7% and 0.9% based on the best-corrected visual acuity (BCVA), respectively. [4] Kailu is in the east of Inner Mongolia, and most of the population is rural. However, Baotou (40°38′00″N, 109°59′00″E) is the biggest City of the Inner Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…VI in school-age students is a major public health problem [2,3,4,5]. Good visual acuity (VA) is critical to students’ well-being and VI has many negative effects on all domains of the development of individuals [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%